2022
DOI: 10.1186/s12888-022-03925-z
|View full text |Cite
|
Sign up to set email alerts
|

Association among calf circumference, physical performance, and depression in the elderly Chinese population: a cross-sectional study

Abstract: Background Depression and sarcopenia are common diseases in the elderly population. However, the association between them is controversial. Based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS) database, a cross-sectional study was conducted to explore the relationship of calf circumference and physical performance with depression. Methods From the 8th wave of CLHLS conducted in 2018, data on calf circumference, physical performance, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
5
0
2
Order By: Relevance
“…(Z. Chen et al, 2022;Cheng et al, 2021;Darroch et al, 2022;de Souza et al, 2021;Delibaş et al, 2021;Gao et al, 2021;He et al, 2022;Jin et al, 2021;Kirk et al, 2021;Kitamura et al, 2020;Kurita et al, 2021;Lee & Lee, 2023;Lin et al, 2022;Lu et al, 2023;Nunes et al, 2021;Suzan et al, 2022;Tan et al, 2022;Zhang et al, 2022). En la tabla 1 se muestran las características y principales resultados de los estudios que incluyeron un análisis transversal.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…(Z. Chen et al, 2022;Cheng et al, 2021;Darroch et al, 2022;de Souza et al, 2021;Delibaş et al, 2021;Gao et al, 2021;He et al, 2022;Jin et al, 2021;Kirk et al, 2021;Kitamura et al, 2020;Kurita et al, 2021;Lee & Lee, 2023;Lin et al, 2022;Lu et al, 2023;Nunes et al, 2021;Suzan et al, 2022;Tan et al, 2022;Zhang et al, 2022). En la tabla 1 se muestran las características y principales resultados de los estudios que incluyeron un análisis transversal.…”
Section: Resultsunclassified
“…Sobre esta línea de investigación, Jin et al (2021), Lu et al (2023), Tan et al (2022) y Zhang et al (2022), encontraron que las alteraciones en alguno de los componentes de la sarcopenia (masa muscular, fuerza y rendimiento físico) incrementaba la probabilidad de presentar síntomas depresivos en los AM.…”
Section: Discussionunclassified
“…Several studies have showed that depression elevates the subsequent risk of physical disability [ [32] , [33] , [34] , [35] ]. However, we found no association between depression and decreased physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to sarcopenia, SO has been linked to frailty and osteoporosis (Fan et al, 2021 ; Chou et al, 2022 ). Moreover, individuals with SO are at greater risk of metabolic disorders and reduced physical performance, such as walking speed, than those with sarcopenia or obesity alone (Sun et al, 2021 ; Tan et al, 2022 ). It was proposed that individuals with SO tended to suffer from impairment of living functions and lower physical capabilities during aging (Hayes and Preacher, 2014 ; Jia et al, 2020 ; Tanaka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%